Effect of chorioamnionitis on necrotizing enterocolitis in preterm infants: a multicenter cohort study - Guo, Xin; Xian, Jiaming; Chen, Xianhong; Li, Meifen; Lin, Fengji; Ma, Defei; Zhang, Rongrong; Zhong, Guichao; Tu, Huiying; Zeng, Shujuan; Kang, Houxin; Pan, Ya; et al. (Frontiers in Pediatrics, 2025)
BackgroundTo explore the association between maternal chorioamnionitis (CAM) exposure and necrotising enterocolitis (NEC) in very preterm infants (VPI) or very low birth weight (VLBWI).MethodsThe aim of this multicentre cohort study was to investigate the impact of maternal CAM and its different staging on VPI or VLBWI NEC in six medical centres in Shenzhen between 2022 and 2023. The primary outcome was NEC (Bell staging ≥ II) and secondary outcomes included NEC or in-hospital mortality. Logistic regression adjusted for confounders identified through directed acyclic graphs (DAG) and literature review. The interaction effect of premature rupture of membranes was assessed using stratification and likelihood ratio tests.ResultsIn the cohort study, the prevalence of CAM was 44.31%, the prevalence of NEC was 5.38%, and the prevalence of NEC or death was 7.69%. Of the 288 participants whose mothers had been exposed to CAM, 1.04% had clinical CAM, 96.53% had histological CAM, and 2.43% were diagnosed with confirmed CAM. CAM was associated with NEC or death (aOR = 1.90, 95% CI 1.02–3.55); the confirmed CAM group showed a stronger association (aOR = 7.14, 95% CI 1.20–42.35). In preterm infants, CAM was significantly associated with NEC or death in cases of preterm membrane rupture (aOR = 2.18, 95% CI 1.07–4.44).ConclusionsThere was a significant positive association between CAM and NEC or death in VLBWs or VPIs, which was mainly from the population with confirmed CAM. In premature rupture of membranes, the association between CAM and NEC or death was more significant.